A LOOK AT THE ART OF PUPPET THEATER - Ma'mura Umarxodjaeva (Journal Park Publishing, 2024)
Today, while theater art is giving way to show business in many countries, the demand and need for Uzbek stage art has not decreased. After all, the stage is a live process. Talent and lack of talent are evident in it. Theater art is a product of imagination and thinking, a means of spiritual growth. Creators of our national theaters participate in international festivals held in many countries such as France, Germany, China, South Korea, Japan, Egypt and win prizes with their new plays. However, Uzbek theater has many undiscovered creative treasures. Puppet theater in particular is as limitless as children's fantasy and as boundless as the creative imagination. Movement in accordance with the characteristics of time is the main criterion of creativity. Because creativity teaches life, if creativity lags behind the audience, how can it be called a teacher.
Keywords: teacher, theater, national dramaturgy, Uzbek theater art, festivals.